Development of Group Counseling with Modeling Techniques to Increase Efficiency in Career Decisions of Students - Siti Mutmainah; I Ketut Gading; I Ketut Dharsana (Bisma The Journal of Counseling, 2021)
This study aims to develop a guidebook for group counseling on modeling techniques to improve self-efficacy in career decision making for vocational students. This research is a type of research and development (R&D). The product acceptance tester of this manual involves 5 experts and practitioners of guidance and counseling. Testing the validity of the content of the manual product using the Lawshe formula and testing the effectiveness by finding the effective contribution (nn effect size) using the Cohen-D formula. The results of the acceptance test data analysis with the Lawshe CVR test obtained a value per item (CVR> 0 or 1) for all items, then the results of the Lawshe CVI analysis obtained a score of 1, then this result means that the value of the content validity of the product content of the group counseling guidebook Modeling technique is high, calculate the effectiveness of the guidebook and get the results 3.17 So based on the value of the effectiveness of the above then according to the criteria. If the value of effect size > 0.50 then the group counseling guide modeling technique is effective to minimize self-efficacy students'in making career decisions. This shows that the level of effectiveness of the modeling technique group counseling guidebook for SMK students is very good, so it is important to develop it for students in school.